The effect of village fund policy implementation on village financial management in improving the effectiveness of village development in Mahakam Ulu District - Rikan Rikan; Syarifah Hudayah; Cornelius Rantelangi (Faculty of Economics and Business Mulawarman University, 2023)
Village financial management must certainly be done with good and accountable management. Good policy implementation in it is influenced by a good management process to achieve something expected when policy implementation is already running. The purpose of this study is to determine the effect of Village Fund Policy Implementation on Village Financial Management in improving the Effectiveness of Village Development Programs in Mahakam Ulu District. This research was conducted using a census survey method of all Village Heads in Mahakam Ulu Regency as many as 50 people. The analysis method uses the Structural Equation Model with AMOS. The results showed that the implementation of Village Fund Policy and Village Financial Management had a direct and significant effect on the effectiveness of the Village Development Program. Then, the implementation of the Village Fund Policy has a direct and significant influence on Village Financial Management. Furthermore, the implementation of Village Fund Policy affects Village Financial Management in improving the Effectiveness of Village Development Programs in Mahakam Ulu District.